Low-Frequency Repetitive Transcranial Magnetic Stimulation Restores Dynamic Functional Connectivity in Subcortical Stroke - Qin, Yin; Liu, Xiaoying; Guo, Xiaoping; Liu, Minhua; Li, Hui; Xu, Shangwen (Frontiers in Neurology, 2021)
Background and Purpose: Strokes are considered an abnormal brain network disease. Previous studies have focused on the resting-state characteristics over the study period, while dynamic recombination remains largely unknown. Thus, we explored differences in dynamics between brain networks in patients who experienced subcortical stroke and the effects of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) on dynamic functional connectivity (dFCs). Methods: Forty-eight patients with subcortical stroke were randomly divided into the LF-rTMS and sham stimulation groups. Resting-state functional magnetic resonance imaging data were collected before(1 month after stroke) and after(3 months after stroke) treatment; 20 age- and sex-matched healthy controls were also included. An independent component analysis, sliding window approach, and k-means clustering were used to identify different functional networks, estimate dFC matrices, and analyze dFC states before treatment. We further assessed the effect of LF-rTMS on dFCs in subcortical stroke patients. Results: Compared to healthy controls, stroke patients spent significantly more time in state I(P=0.043,ES=0.64) and exhibited shortened stay in state II(P=0.015,ES=0.78); the dwell time gradually returned to normal after LF-rTMS treatment(P=0.015,ES=0.55). Changes in dwell time before and after LF-rTMS treatment were positively correlated with changes in the Fugl-Meyer upper extremity assessment scale(pr=0.48,P=0.028). Moreover, stroke patients had decreased dFCs between the sensorimotor and cognitive control domains, yet connectivity within the cognitive control network increased. These abnormalities were partially improved after LF-rTMS treatment. Conclusions: Abnormal changes were noted in temporal and spatial characteristics of sensorimotor domains and cognitive control domains of patients who experience subcortical stroke; LF-rTMS can promote the partial recovery of dFC. These findings offer new insight into the dynamic neural mechanisms underlying effect of functional recombination and rTMS in subcortical stroke. Registration-URL: http://www.chictr.org.cn/index.aspx;Unique.identifier: ChiCTR18000194 52.